University labor unions in Argentina, Brasil, Colombia, México and their resistance to the university counter-reformation - Bauer, Carlos; Paiva, Luis (Sociedad de Historia de la Educación Latinoamericana y la Universidad Pedagógica y Tecnológica de Colombia, 2017)
This work discusses in a comparative way some aspects of history and trajectory of the labor union movements organized by Argentinian, Brazilian, Colombian and Mexican university professors and intends to establish a critical examination of their political role regarding the mishaps imposed by the neoliberal university counter-reformation. They stand out proposals in the defense of higher education of unrestricted, free, and quality access. It also highlights the struggle for university autonomy, as well as its forms of organization, fight flags, main clashes and demands for better salary and working conditions, particularly against the precarious employment. This text is made on the basis of the bibliographical review on the subject of university labor union, it also takes into account the theoretical and methodological contributions developed by the network Associativism and Syndicalism of the Workers in Education (known is Spanish as ASTE), materials produced by the university  labor unions / associations in the countries visited, official documents of the governments or multilateral organizations that are known to influence education policies for higher education, such as the World Bank, and mainly, interviews granted by professors who partake in the life of these public universities.